A Comparative Analysis of Social Capital in the Western Balkan Countries - Golubović, Nataša L; Džunić, Marija; Marinković, Srđan (Industrija, 2014)
The aim of this paper is to investigate, on the basis of comparative analysis of social capital development in Western Balkan countries, availability of different forms of social capital and to identify segments of social capital that represents obstacles to the faster development of these countries. The need for research on social capital in the Balkan countries is conditioned by the fact that apparent differences in the economic performance of these countries, despite more or less similar reform programs, can not be explained solely by traditional factors of growth. Heterogeneity of economic success of these economies is to a great extent determined by the socio-economic structure in which economic institutions are embedded. Balkan countries can not base their development plans solely on the increase of human and physical capital, but must provide high-quality institutional environment. The results of comparative analysis show the specificity of social capital in the Western Balkan countries, which could in brief be described as a lack of trust in institutions and generalized trust, which stands in the way of improving the economic and institutional efficiency, and strong informal networks (ie network capital ) which in most cases represent an obstacle to the reform processes.